The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/iid3.1020
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory approaches in managing lung inflammation in COVID‐19: A double‐edge sword

Geetika Verma,
Manish Dhawan,
AbdulRahman A. Saied
et al.

Abstract: IntroductionThe novel coronavirus infectious disease 2019 (COVID‐19) which is caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has emerged as a gigantic problem. The lung is the major target organ of SARS‐CoV‐2 and some of its variants like Delta and Omicron variant adapted in such a way that these variants can significantly damage this vital organ of the body. These variants raised a few eyebrows as the outbreaks have been seen in the vaccinated population. Patients develop severe respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…SARS-CoV-2 infection induces a cytokine storm (CS) leading to the release of proinflammatory cytokines, such as interleukin (IL)−6, IL-1β, and tumor necrosis factor (TNF)-α, which play an important role in the progression of COVID-19, and the mechanism is mainly related to the interaction between SARS-CoV-2 and immune cells. 26,27 According to research, COVID-19 severity and clinical prognosis are strongly linked to CS. 28 Studies have shown that SARS-CoV-2 can cause damage to the respiratory, neurological, cardiovascular, gastrointestinal, and genitourinary systems of patients, and its most common clinical symptoms include fever, cough, malaise, anorexia, and shortness of breath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 infection induces a cytokine storm (CS) leading to the release of proinflammatory cytokines, such as interleukin (IL)−6, IL-1β, and tumor necrosis factor (TNF)-α, which play an important role in the progression of COVID-19, and the mechanism is mainly related to the interaction between SARS-CoV-2 and immune cells. 26,27 According to research, COVID-19 severity and clinical prognosis are strongly linked to CS. 28 Studies have shown that SARS-CoV-2 can cause damage to the respiratory, neurological, cardiovascular, gastrointestinal, and genitourinary systems of patients, and its most common clinical symptoms include fever, cough, malaise, anorexia, and shortness of breath.…”
Section: Discussionmentioning
confidence: 99%
“…SARS‐CoV‐2 infection induces a cytokine storm (CS) leading to the release of proinflammatory cytokines, such as interleukin (IL)−6, IL‐1β, and tumor necrosis factor (TNF)‐α, which play an important role in the progression of COVID‐19, and the mechanism is mainly related to the interaction between SARS‐CoV‐2 and immune cells. 26 , 27 According to research, COVID‐19 severity and clinical prognosis are strongly linked to CS. 28…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that SARS-CoV-2 causes the release of pro-inflammatory cytokines such as interleukin (IL)-6, IL-1β, and tumor necrosis factor (TNF)-α, which are mediators of lung inflammation, lung damage, fever, and fibrosis; various chemokines have been found to play an important role in disease progression. 13 …”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of these therapeutics in preventing infections and limiting the spreading of the virus has been highly eroded from the early reports ( 94 ), and nowadays, their efficacy is mainly limited to potentially decreasing the disease severity and death in susceptible people ( 95 ). Excess inflammation caused by an overreacting immune system (cytokine storm) is one of the major pathological features in patients with severe COVID-19 ( 96 ). Thus, hypothetically, if exposure to the mRNA-LNP vaccine leads to a dampened systemic inflammatory response, that may explain why vaccination also reduced disease severity in the case of the delta and omicron variants, in which case the antibodies induced by the original vaccines were not ( 97 ), or minimally neutralizing ( 98 ).…”
Section: Efficacymentioning
confidence: 99%